Upaya Peningkatan Minat Baca Kalangan Remaja dengan Pengadaan Kursi Ergonomis di Dukuh Kalitan Kartasura - Brillian Nur Diansari; Muhammad Syarqim Mahfudz; Fertilio Dwyanton; Muhammad Abdul Majid (UNIB Press, 2022)
The development of science and technology that is increasing rapidly at the time causes the development of information to grow rapidly. Dukuh Kalitan is one area that has a young generation with low interest in reading. One of the reasons for this lack of interest in reading is the lack of education about the importance of reading for the younger generation. Another factor is found in the field is the unavailability of reading facilities in Dukuh Kalitan. The solution offered from these problems is the procurement of an ergonomic reading chair. The reading chair will be made based on the user’s body dimensions. The goal is to make users feel comfortable, prevent risks that occur due to workloads, and increase user satisfaction. The method used through a combination of empowerment includes methods: increasing knowledge in the form of counseling and procuring products in the form of an ergonomic reading chair. The procurement of ergonomic reading chairs is carried out by measuring the user’s body dimensions using anthropometry and percentile calculations. The design of this ergonomic reading chair uses a design type for adjustable use. The conclusions that can be drawn are as follows: (1) the principle of ergonomics is very relevant in designing an ergonomic reading chair that fits the dimensions of the user’s body; (2) there are 7 dimensions for designing an ergonomic reading chair for teenagers in Dukuh Kalitan, namely: popliteal height, popliteal buttocks, hip width, sitting shoulder height, shoulder width, sitting elbow height and forearm length.